Kepribadian Atlet PON Bengkulu Menuju PON XX Papua 2021 - yahya eko nopiyanto; septian raibowo; gilang ugo prabowo; Novriansyah Novriansyah (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The purpose of this research was to determine the personality of Bengkulu athletes who will compete in PON Papus 2021. The aspects of personality studied consist of achievement, adaptability, competitiveness, conscientiousness, visualization, intuition, goal setting, managing pressure, self efficacy, fear of failure control, flow, management, emotions, self-talk, self awareness, ethics, empathy, relationships, aggressiveness, power, impressions managements. This research method is quantitative descriptive. The subjects of this research were all Bengkulu athletes who will participate in PON XX Papua 2021. The instrument used in this research was sport personality questionnaire (SPQ-20). The data analysis technique in this study used quantitative precentage. The results revealed that of the 21 aspects studied there were 13 personality aspects included in the study high category and 8 aspects fall into the medium category. The results of the research were expected to be able to become a reference and description of the athlete's personality. Recommended for athletes who were still in the moderate category so that they can be trained properly so that they can maximize psychological skills, especially personality.